Kesejahteraan psikologis pada remaja dengan orangtua bercerai: Dapatkah ditingkatkan dengan pelatihan memaafkan? Psychological well-being in adolescents with divorced parents: Can it be improved by forgiveness training? - Widiastuti, Netty; Soeharto, Triana Noor Edwina Dewayani; Purnamasari, Santi Esterlita (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2023)
Divorce has many negative impacts on teenagers, such as low psychological well-being caused by negative emotions that arise as a result of parents' divorce. This study aims to determine the effectiveness of forgiveness training to improve psychological well-being in adolescents with divorced parents. This study uses the quasi-experimental design Pretest-Posttest Control Group with Follow-up Design. The study subjects were 12 adolescents with divorced parents, consisting of 4 males and 8 females, with a male psychological well-being score in the medium-low category. Subjects were divided into 2 groups randomly, consisting of 6 subjects in the experimental group and 6 subjects in the control group. The experimental group was given intervention in the form of forgiveness training for 3 meetings and the control group was given a video on the power of forgiveness after the research was complete. Data collection was carried out using the Psychological Well-being Scale (α – 0,919) and the Forgiveness Scale (α = 0,886). The data analysis method used is the Independent Sample T-test and Paired Sample T-test. Based on these results, it can be interpreted that training to forgive can improve the psychological well-being of adolescents with divorced parents.